2018
DOI: 10.1007/s00234-018-2137-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of normal-appearing white matter in multiple sclerosis using quantitative susceptibility mapping in conjunction with diffusion tensor imaging

Abstract: Purpose Quantitative susceptibility mapping (QSM) is influenced by iron as well as myelin, which makes interpretation of pathologic changes challenging. Concurrent acquisition of MR sequences that are sensitive to axonal/myelin integrity, such as diffusion tensor imaging (DTI), may provide context for interpreting quantitative susceptibility (QS) signal. The purpose of our study was to investigate alterations in normal-appearing white matter (NAWM) in multiple sclerosis (MS) using QSM in conjunction with DTI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 49 publications
(83 reference statements)
2
14
0
Order By: Relevance
“…For example, myelin estimation based on simultaneous T1/T2 relaxometry and proton density mapping correlated strongly with histological myelin as seen in post-mortem MS brain samples (Ouellette et al, 2020). Another study demonstrated that quantitative susceptibility provided additional myelin information in brain NAWM of MS patients, independent of FA and RD (Yu et al, 2019). Further, pre-operative myelin mapping using T1/T2 ratio showed the potential to predict outcomes of trigeminal neuralgia following Gamma knife radiosurgery, while FA and RD demonstrated similar values in this prediction as estimators of pre-operative axons (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 88%
“…For example, myelin estimation based on simultaneous T1/T2 relaxometry and proton density mapping correlated strongly with histological myelin as seen in post-mortem MS brain samples (Ouellette et al, 2020). Another study demonstrated that quantitative susceptibility provided additional myelin information in brain NAWM of MS patients, independent of FA and RD (Yu et al, 2019). Further, pre-operative myelin mapping using T1/T2 ratio showed the potential to predict outcomes of trigeminal neuralgia following Gamma knife radiosurgery, while FA and RD demonstrated similar values in this prediction as estimators of pre-operative axons (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 88%
“…Brain iron levels are known to be disturbed in multiple sclerosis (MS) (Filippi et al, 2019; Hagemeier, Geurts, & Zivadinov, 2012; Zecca, Youdim, Riederer, Connor, & Crichton, 2004). Most studies reported increased iron concentrations in the deep gray matter (DGM) (Stankiewicz, Neema, & Ceccarelli, 2014) and around plaques (Craelius, Migdal, Luessenhop, Sugar, & Mihalakis, 1982), and reduced iron concentrations within lesions (Haider et al, 2014; Kutzelnigg et al, 2005; Laule et al, 2013; Yao et al, 2012; Yao et al, 2014), in the normal‐appearing white matter (WM) (Hametner et al, 2013; Paling et al, 2012; Popescu et al, 2017; Yu et al, 2018), and in the thalamus (Bergsland et al, 2018; Burgetova et al, 2017; Khalil et al, 2015; Louapre et al, 2017; Pontillo et al, 2019; Schweser et al, 2018; Uddin, Lebel, Seres, Blevins, & Wilman, 2016; Zivadinov et al, 2018). The literature considers findings of increased region‐average iron concentrations as evidence for iron influx (Bergsland et al, 2019; Ndayisaba, Kaindlstorfer, & Wenning, 2019; Williams, Buchheit, Berman, & LeVine, 2012), whereas it is less clear how to interpret reduced iron concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Based on such low resolution, it is difficult for a conventional brain MRI to accurately reflect the state of damage of a relatively small number of brain cells. Furthermore, it has been shown that brain lesions of several brain diseases other than DAI also cannot be detected by conventional MRI [29,30].…”
Section: Problem 2: the Low Sensitivity Of Conventional Brain Mri In mentioning
confidence: 99%